-3(x-1)+8(x-3)=6x+7

Simple and best practice solution for -3(x-1)+8(x-3)=6x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-1)+8(x-3)=6x+7 equation:


Simplifying
-3(x + -1) + 8(x + -3) = 6x + 7

Reorder the terms:
-3(-1 + x) + 8(x + -3) = 6x + 7
(-1 * -3 + x * -3) + 8(x + -3) = 6x + 7
(3 + -3x) + 8(x + -3) = 6x + 7

Reorder the terms:
3 + -3x + 8(-3 + x) = 6x + 7
3 + -3x + (-3 * 8 + x * 8) = 6x + 7
3 + -3x + (-24 + 8x) = 6x + 7

Reorder the terms:
3 + -24 + -3x + 8x = 6x + 7

Combine like terms: 3 + -24 = -21
-21 + -3x + 8x = 6x + 7

Combine like terms: -3x + 8x = 5x
-21 + 5x = 6x + 7

Reorder the terms:
-21 + 5x = 7 + 6x

Solving
-21 + 5x = 7 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-21 + 5x + -6x = 7 + 6x + -6x

Combine like terms: 5x + -6x = -1x
-21 + -1x = 7 + 6x + -6x

Combine like terms: 6x + -6x = 0
-21 + -1x = 7 + 0
-21 + -1x = 7

Add '21' to each side of the equation.
-21 + 21 + -1x = 7 + 21

Combine like terms: -21 + 21 = 0
0 + -1x = 7 + 21
-1x = 7 + 21

Combine like terms: 7 + 21 = 28
-1x = 28

Divide each side by '-1'.
x = -28

Simplifying
x = -28

See similar equations:

| 16p^2-40p+25=0 | | 36=.5x+x+(2x+1) | | 2x^2+15y-27=0 | | (6x-11)(6x+11)= | | 5x+3x=30-2x | | =16x^2+11x-14 | | 3x+12-9x=17-19x+13x-5 | | (x+4)(x^2-4x+16)= | | 6-2(2w+1)=4w-2(4+w) | | 4d^2+0b-25=0 | | -n+4(1+7n)=15+8 | | 8x-(6x+5)=5 | | 25x+3=23 | | 5a-3=3+2a | | 6.3-x=10.7 | | 4d^2-25=0 | | 7=-3-6x+8x | | 0.1x-1.2=-2 | | 17=m-1+2m | | -4(5x-7)=3(4x+5) | | (6-2w)-(4w+w)+1= | | -1.5+k=8.2 | | 3x-5=x-1 | | x(x+8)-12(x+8)=0 | | 5k^2-2k-7=0 | | 3x-4y+2y=11 | | (-x)(-y)=-xy | | 5p+18=6(p+8) | | 35x+3=28x+2 | | 4b-7=-10b | | 18x^5+15x^4z-75x^3z^2=0 | | 4m+-24= |

Equations solver categories